2015
DOI: 10.1159/000440652
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Dutch, Finnish and British Screening Guidelines in a Cohort of Children with Growth Failure

Abstract: Aims: To evaluate three guidelines for selecting short children for diagnostic workup in a general pediatric clinic. Methods: All patients (n = 131) aged 3.00-9.99 years who were referred for growth failure to a general pediatric clinic were evaluated for their medical history and growth and examined. All of them underwent the same standardized diagnostic workup. Retrospectively, the criteria for the diagnostic workup from three guidelines (proposed in the Netherlands, Finland and the UK) were applied, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 18 publications
(35 reference statements)
4
38
1
3
Order By: Relevance
“…The reported prevalence of GHD in children referred for GF to a paediatric (endocrine) clinic also varies. In Dutch studies the prevalence was between 0.5-3% (24,25,26) and in other studies prevalences between 0 and 23% were reported (27,28,29,30,31,32,33,34). For this analysis we estimated the general prevalence of GHD in children referred for GF at 2%, in line with a recent publication (35), but this percentage may differ between a general and academic paediatric clinic.…”
Section: Prevalence Of Ghd and Its Subcategories In Children Referredmentioning
confidence: 80%
“…The reported prevalence of GHD in children referred for GF to a paediatric (endocrine) clinic also varies. In Dutch studies the prevalence was between 0.5-3% (24,25,26) and in other studies prevalences between 0 and 23% were reported (27,28,29,30,31,32,33,34). For this analysis we estimated the general prevalence of GHD in children referred for GF at 2%, in line with a recent publication (35), but this percentage may differ between a general and academic paediatric clinic.…”
Section: Prevalence Of Ghd and Its Subcategories In Children Referredmentioning
confidence: 80%
“…The false-positive rate was low. Analysis of these criteria led to an algorithm for referral of children with growth disorders [28], which has recently been updated [34] (fig. 1).…”
Section: Criteria For Referral From Primary Carementioning
confidence: 99%
“…Auxological referral criteria in the Dutch, Finnish and UK primary care systems were assessed against a population of short stature patients aged between 3 and 9.9 years, referred to a general paediatric clinic in the Netherlands [34]. The training of primary care nurses in measurement techniques is essential.…”
Section: Comparison Of Growth Monitoring In the Netherlands Finland mentioning
confidence: 99%
“…There is little difference in the physical builds between children in 2000 and children today, so these data are generally used. In contrast, growth failure is difficult to define (Stalman et al, 2015), and hence, various studies have defined it differently. For example, Jonathan (2004) defined it as growth deceleration (falling across major percentiles on the growth curve).…”
Section: Judgement From Height Datamentioning
confidence: 99%